THE INFLUENCE OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE TOWARDS EMPLOYEE WORK MOTIVATION 3 STAR HOTEL IN MEDAN - Setiawan, Abdi; Lubis, Arlina Nurbaity; Absah, Yeni; Sembiring, Beby Karina F. (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to determine whether the leadership style and organizational culture influence employee motivation at Sampali Asri PT Kurnia Medan. This research using descriptive data analysis, multiple regression analysis with t-test (test partial), F test (simultaneous test) and test the coefficient of determination (R2). This research test equipment using multiple linear regression model. The conclusion that can be drawn from the test results, the stimulatory and partial leadership style and organizational culture influence employee motivation. The implications of the results of this research are able to explain that leadership and organizational culture are closely related to motivation, because the success of a leader in moving other people to achieve the goals that have been set is very dependent on authority, and also the leader in creating motivation within each person. Subordinate.